Pemanfaatan Limbah Tandan Kosong Kelapa Sawit Menjadi Pupuk Kompos Di Desa Suka Damai Kecamatan Tunggal Jaya Musi Banyuasin - Ita Emilia; Liani Ardila; Putri Anggraini (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2024)
Processing palm oil into palm oil produces solid waste in the form of empty palm fruit bunches (TKKS) which will cause environmental pollution. The aim of this research is to find out how to manage waste from empty oil palm fruit bunches into compost which is needed by plants as a natural nutrient. The research method uses experimental methods. The results of the research resulted in TKKS being able to be processed into compost by fermentation.